1962
DOI: 10.1002/art.1780050606
|View full text |Cite
|
Sign up to set email alerts
|

Synovial fluid lipids in normal individuals and patients with rheumatoid arthritis

Abstract: Normal human synovial fluid contains trace amounts of phospholipids and cholesterol. Phospholipid composition is similar to that in serum. Rheumatoid synovial fluid contains increased amounts of phospholipid, cholesterol, and neutral lipids. I n most cases the concentration is 40 to 60 per cent of that found in simultaneously collected serum specimens. A direct relationship appears to exist between total synovial fluid protein and lipid concentration. No relationship could be established between lipid content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1965
1965
1993
1993

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…1.5-3.1 mM [6] which are approximately 2-fold greater than those of healthy human serum samples. However, in 'H Hahn spin-echo spectra of RA SF (Fig.…”
Section: Tao-chs I 'mentioning
confidence: 75%
“…1.5-3.1 mM [6] which are approximately 2-fold greater than those of healthy human serum samples. However, in 'H Hahn spin-echo spectra of RA SF (Fig.…”
Section: Tao-chs I 'mentioning
confidence: 75%
“…It has been suggested that LDL is a major plasma regulator of HeLa cell adhesion to glass (62), which is a negatively charged surface like monosodium urate crystals. In addition, there is evidence that human serum enhances the stimulation by urate crystals ofnonmitogenic synovial fibroblast responses in vitro (63,64 (19,(55)(56)(57)(58), LDL may well represent an important factor in modulation of gouty inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…This work indicates that the supply of lipids to cartilage, through the synovial fluid, is responsive to the dietary supply. Lipid content of synovial fluid has been shown to be low and to differ qualitatively from that of blood (5). Articular chondrocytes can synthesize oleic acid from carbohydrate sources, but linoleic and, indirectly arachidonic acids in the cells must be supplied primarily from synovial fluid.…”
Section: Discussionmentioning
confidence: 99%